An efficient privacy‐enhanced attribute‐based access control mechanism - Xu, Yang; Zeng, Quanrun; Wang, Guojun; Zhang, Cheng; Ren, Ju; Zhang, Yaoxue (Concurrency and computation, 2020)
Summary Owing to the rapid progress of network researching, attribute‐based access control (ABAC) has attracted more and more attention due to its appreciable expressiveness, flexibility, and scalability. Unfortunately, collecting user attributes is necessary to complete the standard ABAC decision process, which increases the risk of privacy disclosure. This problem increases public doubts about ABAC and hinders its popularization. In this paper, a privacy‐protected and efficient attribute‐based access control (EPABAC) scheme is proposed to prevent the privacy leakage of access subject in the decision‐making process of ABAC by introducing a novel hash‐based binary search tree. The analyses and experimental evaluations show that the EPABAC achieves user privacy protection in the decision‐making process with acceptable additional computing overhead.